(untitled) (Bangladesh Journal of Botany, 2012)
Ramsagar, an artificial lake of Dinajpur district has been investigated limnologically. Mean alkalinity, DO, pH, TDS and conductivity of the lake were 0.50 meq/l, 7.99 mg/l, 6.73, 10.66 mg/l and 73.66 ?S/cm, respectively. The concentration of soluble reactive phosphorus and silicate was very low. Mean value of the former parameter was 3.16 ?g/l and the latter was 0.77 mg/l. Nitrate-nitrogen concentration was < 0.1 mg/l. Phytoplankton biomass as chl a was 5.92 ?g/l and that of phaeopigment 3.65 ?g/l. Phytoplankton flora of the lake was found to be dominated by desmids. The dominant species were Staurastrum coarctatum var. subcurtum (59.35×104, ind/l); S. subgracillimum var. tortum (44.83×104 ind/l) and S. leptacanthum (29.06×104 ind/l). Among the blue-green algae, Anabaena utermöhlii was dominant. Chlorococcales was represented by seven species. The total density of phytoplankton was 163.53×104 ind/l. Considering the overall limnological characteristics, the lake could be characterized as acidic and nutrient poor. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11091 Bangladesh J. Bot. 41(1): 119-121, 2012 (June)